Students' Mathematical Connection Ability in Solving Higher Order Thinking Skills Problems Based on Jambi Culture - Vrasetya, Arshinta; Nasution, Eline Yanty Putri (Plusminus: Jurnal Pendidikan Matematika, 2024)
Kemampuan koneksi penting sebagai bagian dari keterampilan berpikir tingkat tinggi. Penelitian ini bertujuan mengeksplorasi kemampuan koneksi matematis siswa dalam menyelesaikan soal HOTS berbasis budaya Jambi. Penelitian studi kasus ini melibatkan 32 siswa dengan tipe kepribadian sensing dan intuiting. Instrumen penelitian mencakup tes kepribadian MBTI (Myers-Briggs Type Indicator), lembar tes soal HOTS, dan wawancara. Data dikumpulkan melalui triangulasi sumber dan waktu, dianalisis menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan kemampuan koneksi matematis siswa dengan tipe kepribadian sensing lebih baik (70%) daripada tipe intuiting (56,25%). Temuan ini mengindikasikan siswa dengan tipe sensing lebih efektif dalam mengaitkan dan menerapkan konsep matematika pada soal HOTS berbasis budaya Jambi, sementara siswa dengan tipe intuiting menghadapi kesulitan dalam membangun koneksi matematis, yang mempengaruhi akurasi jawaban mereka. Dengan demikian, tipe kepribadian memiliki pengaruh signifikan terhadap kemampuan siswa dalam mengintegrasikan dan menerapkan pengetahuan matematika dalam situasi kompleks. Connection abilities are important as part of higher order thinking skills. This study aims to explore students' mathematical connection skills in solving HOTS problems based on Jambi culture, with a focus on the Kajang leko traditional house and the padamaran cake typical of Jambi. This research used a case study approach involving 32 students with sensing and intuiting personality types. The research instruments included MBTI (Myers-Briggs Type Indicator) personality tests, HOTS question test sheets, and interviews. Data were collected through triangulation of sources and time, then analyzed using data reduction, data presentation, and conclusion drawing. The results showed that students with sensing personality type had better mathematical connection ability (70%) than students with intuiting type (56.25%). This finding indicates that students with the sensing type are more effective in connecting and applying mathematical concepts to Jambi culture-based HOTS questions, while students with the intuiting type face difficulties in building mathematical connections, which affects the accuracy of their answers. Thus, personality type has a significant influence on students' ability to integrate and apply mathematical knowledge in complex situations.